Atlantic Landscapes: Connecting Place and People in the Modern World. (2nd September 2015) - Finch, Jonathan
Abstract : This article is based on the first archaeological study to reconnect landscapes in the United Kingdom and Caribbean as legacies of a single landowning family: the Lascelles of Harewood House in West Yorkshire, England. It seeks to trace the lines of modernity across the Atlantic and to understand relationships on two sides of the trans-Atlantic trade. It employs multi-scalar and multi-sited archaeology to suggest how analysis can combine a local empiricism and a global context to offer a distinctive perspective. Although the artifacts recovered in each location are very different in terms of date, context, use, and deposition, their relational nature and connections make their meanings interdependent. The fieldwork in Barbados was supported by a British Academy Small Grant (R1357801). Research into the Harewood estate landscape was supported by an AHRC CDA with the Harewood House Trust.